Reconfigurable infrared hyperbolic metasurfaces using phase change materials. Issue 1 (December 2018) - Folland, T.; Fali, A.; White, S.; Matson, J.; Liu, S.; Aghamiri, N.; Edgar, J.; Haglund, R.; Abate, Y.; Caldwell, J.
Abstract Metasurfaces control light propagation at the nanoscale for applications in both free-space and surface-confined geometries. However, dynamically changing the properties of metasurfaces can be a major challenge. Here we demonstrate a reconfigurable hyperbolic metasurface comprised of a heterostructure of isotopically enriched hexagonal boron nitride (hBN) in direct contact with the phase-change material (PCM) single-crystal vanadium dioxide (VO2 ). Metallic and dielectric domains in VO2 provide spatially localized changes in the local dielectric environment, enabling launching, reflection, and transmission of hyperbolic phonon polaritons (HPhPs) at the PCM domain boundaries, and tuning the wavelength of HPhPs propagating in hBN over these domains by a factor of 1.6. We show that this system supports in-plane HPhP refraction, thus providing a prototype for a class of planar refractive optics. This approach offers reconfigurable control of in-plane HPhP propagation and exemplifies a generalizable framework based on combining hyperbolic media and PCMs to design optical functionality. Here, the authors demonstrate that the dispersion of hyperbolic phonon polaritons can be controlled using the permittivity changes inherent in the different phases of phase change materials. This enables direct launching, reflection, transmission and refraction at the phase change material domain boundaries.